Empowerment Strategy for Muslim Entrepreneur Community in Jambi City - Syaifudin, Alfi; Indrawijaya, Sigit; Ridhwan, Ridhwan; Mufaddhal, Zaidan (Najaha Iqtishod: Journal of Islamic Economic and Finance, 2023)
This research aims to analyze and create alternative strategies for the GENPRO and IPEMI communities as communities oriented towards Muslim entrepreneurs in increasing the empowerment of their members. The type of research is descriptive quantitative, and uses the Quantitative Strategic Planning Matrix (QSPM) method. By using three strategy formulations, namely the data collection stage, the data matching stage, and the decision-making stage. It is hoped that the results of this study can become the basis for policies in increasing the empowerment of community members. The results showed that from the calculation of IFE and EFE analysis based on 65 respondents, the main strength is the routine coaching of members, while the main weakness is insufficient facilities and infrastructure. And the main opportunity is that members always participate in determining the direction of the community, while the main threat is that many members join more than one community. As well as the results of the QSPM calculation by 4 Respondents as those who determine the priority of policies to be taken, 7 strategies were chosen with the first priority being to accommodate cooperation between members by integrating all potential and productive resources with a TAS score of 5.596.